2016
DOI: 10.7196/ajhpe.2016.v8i1.422
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stressors of oral hygiene students in the dental environment

Abstract: Background. University students are exposed to a multitude of stressors that may impact on their performance. The nature of health sciences education generally involves early engagement with patients and communities, which may add to the stressors inherent to university life. There is sparse information on stressors in the oral hygiene educational environment. Objective. To determine perceived stressors and the level of burnout among oral hygiene students at the University of the Western Cape, Cape Town, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 26 publications
4
38
1
Order By: Relevance
“…[1][2][3][4][5][6] Living accommodation and personal factors were not particularly stressful DES domains for either the UK or Australian DHDTS, and were similar to a previous UK study. 7 This present study also showed a trend that both UK and Australian DHDTS perceived the which is in contrast to the recent SA study of perceived stress in DHDTS, 9 which showed that third-year students reported individual clinical factors, and not academic factors, as their top sources of stress. However, we must show caution in direct comparisons with this study, as the SA researchers modified the DES from a 5-point scale which was used in the current study, to a 3-point scale, which has less range.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…[1][2][3][4][5][6] Living accommodation and personal factors were not particularly stressful DES domains for either the UK or Australian DHDTS, and were similar to a previous UK study. 7 This present study also showed a trend that both UK and Australian DHDTS perceived the which is in contrast to the recent SA study of perceived stress in DHDTS, 9 which showed that third-year students reported individual clinical factors, and not academic factors, as their top sources of stress. However, we must show caution in direct comparisons with this study, as the SA researchers modified the DES from a 5-point scale which was used in the current study, to a 3-point scale, which has less range.…”
Section: Discussioncontrasting
confidence: 96%
“…Although the domain of the educational environment, which included items such as criticism about academic or clinical work, approachability of staff and expectation vs reality of dental school, was not perceived as stressful to the UK DHDTS, it was, however, significantly higher ( P < .002) for the Australian DHDTS. In particular, both years 2 and years 3 Australian DHDTS reported criticism about academic or clinical work as a high source of stress (which was similar to that reported by DHDTS in the SA study), with approachability of staff an additional high source of stress to the year 3 students (Table ). These were also the same sources of stress reported by third‐year dental students in a recent Australian study .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…[2][3][4] However, there are gaps in the literature when it comes to exploring stress among other members of the dental team, for example dental hygiene and dental therapy students (DHDTS), who are educated in a similar environment to dental undergraduate students. 5 Most studies exploring dental student stress have equated psychological well-being with the presence or absence of stress, or psychological disorders such as depression. [6][7][8] However, studies have also shown that there are multiple dimensions which contribute to a sense of positive psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%